2013
DOI: 10.1016/j.jamcollsurg.2013.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Reconstruction of Oncologic Sternectomy Defects Based on Surgical Outcomes

Abstract: Background The optimal strategy for oncologic sternectomy reconstruction has not been well characterized. We hypothesized that the major factors driving the reconstructive strategy for oncologic sternectomy include the need for skin replacement, extent of the bony sternectomy defect, and status of the internal mammary vessels. Study Design We reviewed consecutive oncologic sternectomy reconstructions performed at The University of Texas MD Anderson Cancer Center over a 10-year period. Regression models analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 16 publications
1
16
0
Order By: Relevance
“…In the large populationbased study of Scandinavian Sarcoma Group, is clearly demonstrated the influence of wide free margins on survival; patients radically treated have higher probability of survival at 10 years (92%) compared with intralesional resections (13). Also others authors previously showed a better outcome in term of OS for patients surgically treated without margin involvement (1,19,22). In our report, the DFS is negatively influenced by margins; actually patients with incomplete resection developed early local or distant recurrence.…”
Section: A B a B Csupporting
confidence: 68%
“…In the large populationbased study of Scandinavian Sarcoma Group, is clearly demonstrated the influence of wide free margins on survival; patients radically treated have higher probability of survival at 10 years (92%) compared with intralesional resections (13). Also others authors previously showed a better outcome in term of OS for patients surgically treated without margin involvement (1,19,22). In our report, the DFS is negatively influenced by margins; actually patients with incomplete resection developed early local or distant recurrence.…”
Section: A B a B Csupporting
confidence: 68%
“…Sternum resection for treatment of skin cancer is very rare. With a series of 49 cases, Butterworth et al [1] reported that the main cause of sternectomy was involvement of sternum metastatic tumors and, secondly, sarcomas. No case with skin tumors was described among the patients, who were mostly females.…”
Section: Resultsmentioning
confidence: 99%
“…The sternum is an unusual anatomical site for cancers, making sternectomy for oncologic resections rare [1]. The main indication of sternectomy is surgical treatment of infectious complications after cardiovascular and thoracic surgery, which involves a transsternal approach.…”
Section: Introductionmentioning
confidence: 99%
“…We propose a new material for thoracic wall reconstruction and particularly for sternum. Several drawbacks have been reported for biomaterials used in chest wall reconstruction over the past 30 years:[ 2 ] erosion of adjacent structures, rupture and migration, infection, or immunological reaction. During the past 5 years, custom-made titanium sternal implants, sternal allografts, and mesh have been associated with advantages over other materials.…”
Section: Discussionmentioning
confidence: 99%